Comparison between the widely used magnetically controlled capsule gastroscopy and conventional gastroscopy: a meta-analysis - Hu, Jinlong; Wang, Xinyue; Sun, Siyu (Minimally invasive therapy and allied technologies, 2022)
We systematically evaluated the difference in diagnostic accuracy, check time, and adverse effects between magnetically controlled capsule gastroscopy (MCCG) and conventional gastroscopy in patients with gastric disorders. PubMed, Embase, Cochrane, CKNI and Wanfang Data were searched for studies dated prior to 30 January 2020. We used the QUADAS criteria for quality evaluation. We extracted the diagnostic rate, check time, and adverse events from the studies, then used STATA15.0 to calculate variables (sensitivity, specificity, positive likelihood ratio [LR + ], negative likelihood ratio [LR − ] and diagnostic odds ratio), draw forest plots and SROC curves, and completed sensitivity analysis. A total of 278 titles were identified after an initial search and nine studies with 1,146 individuals were included in the analysis. The pooled sensitivity, specificity, LR + and LR − of MCCG in detecting gastric disorders were 90%, 92%, 10.6, and 0.11, respectively. A ROC curve was drawn with Q = 0.9060 and AUG = 0.96. The diagnostic odds ratio was 93. No significant difference in diagnosis accuracy was demonstrated between MCCG and conventional gastroscopy. The MCCG had a longer check time than conventional gastroscopy and the adverse events occurrence rate was lower. MCCG is a convenient and reliable examination method for gastric diseases.